2008
DOI: 10.1590/s1415-54192008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Estudo in vivo e in vitro com e sem termociclagem, da resistência ao cisalhamento de braquetes colados com fonte de luz halógena

Abstract: OBJETIVO: avaliar a resistência de braquetes metálicos colados em dentes humanos com resina polimerizada com luz halógena por meio de ensaios mecânicos de cisalhamento. METODOLOGIA: para este estudo foram realizados ensaios in vivo com dinamômetro portátil digital e in vitro com máquina de ensaios mecânicos universal com e sem termociclagem, complementado pelo Índice de Adesivo Remanescente (IAR). Braquetes Edgewise Standard (Abzil) foram colados utilizando adesivo Transbond Plus Self Etching Primer (SEP) e Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
2
11
1
2
Order By: Relevance
“…In this study it was found that the polymerization shrinkageis similar in both methods, since there was no statistically significant difference as regards microleakage with SonicFill TM and Filtek TM SupremeXTE. The same operator performed all restorative procedures, to reduce human operator error, as some authors have recommended [10,17,20,30]. The specimens were stored in distilled water at 37˚C for one week [2,14] and after thermocycling 500 cycles between 5˚C and 55˚C with a dwell time of 30 seconds [10,22,29,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study it was found that the polymerization shrinkageis similar in both methods, since there was no statistically significant difference as regards microleakage with SonicFill TM and Filtek TM SupremeXTE. The same operator performed all restorative procedures, to reduce human operator error, as some authors have recommended [10,17,20,30]. The specimens were stored in distilled water at 37˚C for one week [2,14] and after thermocycling 500 cycles between 5˚C and 55˚C with a dwell time of 30 seconds [10,22,29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Composite restorations are exposed to various influences in the oral cavity, and therefore to evaluate microleakage meth-ods to reproduce these features are required. Storage in water is the most common artificial ageing technique, as mentioned by Amaral et al and Yuasa et al [22,23] Another widely used method is thermocycling [11,23,30]. For Geerts et al thermocycling is the only in vitro test for stimulating thermal stress in teeth [32].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there are reports, such as that by Penido et al 20 , of good performance with self-etching primers. These authors showed acceptable performance of this material when evaluated in vitro, with or without thermal cycling after bonding (results of 7.11 and 7.35 MPa, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…The authors of the present study believed that with a smaller sample size, group GTF might have presented statistically higher results than group GSAF. This is because the material in group GTF had a conventional adhesive system in which an acid was used with a pH lower than that contained in self-etching adhesive systems, such as GSAF, favoring micro-mechanical interlocking, and consequently, the bond strength to tooth enamel [18][19][20] . Self-etching adhesive agents do not require the separate application of an acid to produce porosity in the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to emphasize that recent studies comparing in vivo with in vitro bond strength have shown that the values obtained in vivo proved to be significantly lower than those obtained in vitro. 5,13 Based on the results, Penido et al 13 stressed the importance of evaluating the acceptable values of bond strength of orthodontic accessories obtained through mechanical testing.…”
Section: E7mentioning
confidence: 99%